Pengaruh Zona Integritas-Wilayah Bebas Korupsi (ZI-WBK) Terhadap Motivasi Kerja Pegawai di KPP Pratama Lahat Sumatera - Putri, Chike Kurnia; Haptari, Vissia Dewi (JEMAP, 2025)
Corruption Zone (ZI-WBK) predicate is expected to boost employee motivation through improved work culture and professionalism. This study aims to examine the effect of the ZI-WBK predicate on employee motivation at KPP Pratama Lahat. Research data were collected from 63 employees through questionnaires and in-depth interviews. The study employs a quantitative method with a pretest-posttest design, supported by inferential statistical analysis and a qualitative approach. The findings revealed a significant increase in employee motivation after KPP Pratama Lahat achieved the ZI-WBK predicate. Additionally, positive changes in work culture, including enhanced responsibility and professionalism, were observed. The study concludes that the ZI-WBK predicate contributes to bureaucratic reform and public service quality improvement